Exploring the Meaning of Therapeutic Horticulture for Anishinabek Youth in a Brief Residential Treatment Unit: A Community Engagement CSL Case Study - Nelson, Connie H.; Uvanile, Michelle; Vinni, Judi; Schiff, Rebecca (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2020)
This paper explored community-university engagement that integrated a short-term treatment facility for Indigenous youth, a social enterprise organization that focused on healing through horticulture therapy experiences and an interdisciplinary academic team. The focus was to discover whether a horticulture therapy (HT) approach held promise in terms of an appropriate way to expand community service-learning (CSL) with Indigenous peoples and to encourage more diversity of voices in community service-learning experiences. Youth participants took part in a photovoice study and further semi-structured interviews to document their perspectives on the meaning of their horticultural experiences. Findings revealed that youth valued the overall HT experience itself; being connected to the gardens and nature and the social interactions exploring spirituality and the self were significant and meaningful for them. Further, findings demonstrated that a collaborative partnership that engaged multiple service agencies to explore novel ways for engaging youth in healing activities with a university team that guided the research approach holds promise as a CSL with Indigenous youth. We conclude with recommendations on the significance of community-university engagement in delivering therapeutic horticulture programs for Indigenous youth as a community service-learning initiative.